2004
DOI: 10.1159/000078445
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Rapid Eye Movement Sleep Deprivation and Immobilization Stress on Blood Lymphocyte Subsets in Rats

Abstract: Objectives: There is growing evidence of the relationship between sleep and the immune response. Studies aimed at elucidating the function of rapid eye movement (REM) sleep have found it difficult to separate the effects due to REM sleep deprivation and the effects due to the stress produced by the deprivation procedure. It has been claimed that immobilization is the main stressor that the animals have to face during the deprivation process. In this study, we analyzed the effects of short-term (24 h) and long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
3
10
0
1
Order By: Relevance
“…Regarding the general reduction of immune cell populations in saline-treated mice, these data are in accordance with previous findings showing decreased circulating lymphocyte populations after PSD in humans [25,26] and rodents [17,18,27] . The current study expanded our previous findings [18] by demonstrating that this reduction occurs not only in circulating lymphocytes but also in spleen and in other cell subtypes, such as macrophages, NK cells and dendritic cells.…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the general reduction of immune cell populations in saline-treated mice, these data are in accordance with previous findings showing decreased circulating lymphocyte populations after PSD in humans [25,26] and rodents [17,18,27] . The current study expanded our previous findings [18] by demonstrating that this reduction occurs not only in circulating lymphocytes but also in spleen and in other cell subtypes, such as macrophages, NK cells and dendritic cells.…”
Section: Discussionsupporting
confidence: 92%
“…Overall, both TAIEP and SD rats are associated with an increase in the populations of B cells (CD45+) and NK cells (NK1.1+) in the spleen, and stress is also associated with increased total T cells (CD3+), but in contrast, the SD condition is associated with a decrease in the cytotoxic T cell subpopulation (CD8+CD3+). These results are in agreement with those from Velazquez-Moctezuma, 2004, which reported similar changes with different stressors, and therefore, we can postulate that the overall response of the cell subpopulations depends on the immune system nature of the stressor and the basal condition of the CNS and in this case myelin loss [28]. The major differences of taiep rats in comparison with Sprague-Dawley are that cytokines such as IFN-γ, TNF-α, and were unaltered but IL-1β and IL-10 were downregulated in 1-month-old taiep rats.…”
Section: Discussionsupporting
confidence: 92%
“…described an increase in the number of neutrophils and T lymphocytes after 2 days of total sleep deprivation or 4 days of REM‐sleep deprivation in humans; interestingly, only neutrophils reached basal values after 1 night of sleep recovery, while high numbers of T cells persisted even after 3 nights of sleep recovery. Paradoxically, in a rodent model we found that REM sleep deprivation for 10 days increased the number of NK cells, but decreased the number of T lymphocytes 63 . The reported differences among human studies in the effects of sleep loss on white blood cell counts seem to arise from the length of sleep deprivation and of the age of the participants.…”
Section: Sleep Loss and The Immune Responsementioning
confidence: 59%